Competitiveness as a Key Pathway Linking Inclusive Economic Transformation to MSME Performance in the Trans-Sumatra Toll Road Corridor - Aminudin Azis; Tri Andjarwati; Ulfi Pristiana (Jurnal Ners, 2026)
This study examines the relationship between inclusive economic transformation, competitiveness, and MSME performance along the Trans-Sumatra Toll Road corridor. A total of 394 MSME actors were selected using purposive sampling, and data were collected through Likert-scale questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling. The findings show that inclusive economic transformation has a significant effect on MSME performance, with a t-value of 18.799 and a p-value of 0.000 (p < 0.05). Inclusive economic transformation also significantly influences competitiveness, with a t-value of 22.279 and a p-value of 0.000 (p < 0.05). Competitiveness is proven to be a strong determinant of MSME performance, with a t-value of 26.506 and a p-value of 0.000 (p < 0.05). Inclusive economic transformation also enhances MSME performance through the mediating role of competitiveness, with a t-value of 18.799 and a p-value of 0.000 (p < 0.05). These results confirm that inclusive economic transformation and competitiveness are two mutually reinforcing elements in shaping MSME performance. Theoretically, this study strengthens the concept of inclusive growth, emphasizing the role of access, economic opportunity, and competitive dynamics in improving business performance. Practically, the findings highlight the need for policies that focus on enhancing competitiveness, strengthening business capacity, and expanding market access so that MSMEs can fully benefit from increasingly open economic opportunities. Keywords: inclusive economic transformation, competitiveness, MSMEs performance